Potassium management effects on quantity/intensity relationship of soil potassium under rice-oilseed rape rotation system. Issue 9 (28th July 2020) - Zhu, Dandan; Lu, Jianwei; Cong, Rihuan; Ren, Tao; Zhang, Wenjun; Li, Xiaokun
ABSTRACT: Quantity–intensity curves were used to evaluate the dynamics of soil potassium (K) at different soil depths under different K management. The equilibrium concentration ratio of K (CR0 ) increased with increasing K concentration. K fertilization and straw return increased soil K supplying capacity by increasing CR0, non-specific available K (-∆K0 ) and equilibrium K (CK0 ). The CR0 increase 107%, 392% and 577% at the 0–20 cm layer and 55%, 102% and 131% at the 20–40 cm layer, respectively, under K fertilization, straw return and the interaction of them. The CK0 and -∆K0 at the 0–20 cm layer significantly increased after K fertilization and straw return. The labile K varied from 0.11 to 0.19 cmol kg −1, contributed 85.3% to 107.6% of NH4 OAc extracted K. Soil K potential buffering capacity showed significant differences in soil depths, while little difference was observed under different K management. Th e exchangeable K was meaningless for guiding K application when minimum exchangeable K took up 85.9% to 99.0% of equilibrium exchangeable K. Our results showed K fertilization and straw return was the optimal management to enhance soil K supplying capacity, especially at the 0–20 cm layer. Abbreviations: N: nitrogen; P: phosphorus; K: potassium; RS : straw; Q/I: quantity/intensity; CR0 : equilibrium concentration ratio of K; KL : labile K; non-specifically available K: -∆K0 ; PBC K : potential buffering capacity; EK0 : equilibrium exchangeable K; CK0 : equilibrium solution K; α: magnitude of conversion of added K to exchangeable pool; β: conversion of added K to non-exchangeable K pool; Emin : minimum exchangeable K.